Functional implications of squamosal suture size in paranthropus boisei. Issue 2 (18th November 2013) - Dzialo, Christine; Wood, Sarah A.; Berthaume, Michael; Smith, Amanda; Dumont, Elizabeth R.; Benazzi, Stefano; Weber, Gerhard W.; Strait, David S.; Grosse, Ian R.
ABSTRACT It has been hypothesized that the extensively overlapping temporal and parietal bones of the squamosal sutures in Paranthropus boisei are adaptations for withstanding loads associated with feeding. Finite element analysis (FEA) was used to investigate the biomechanical effects of suture size (i.e., the area of overlap between the temporal and parietal bones) on stress, strain energy, and strain ratio in the squamosal sutures of Pan troglodytes and P. boisei (specimen OH 5) during biting. Finite element models (FEMs) of OH 5 and a P. troglodytes cranium were constructed from CT scans. These models contain sutures that approximate the actual suture sizes preserved in both crania. The FEM of Pan was then modified to create two additional FEMs with squamosal sutures that are 50% smaller and 25% larger than those in the original model. Comparisons among the models test the effect of suture size on the structural integrity of the squamosal suture as the temporal squama and parietal bone move relative to each other during simulated premolar biting. Results indicate that with increasing suture size there is a decreased risk of suture failure, and that maximum stress values in the OH 5 suture were favorable compared to values in the Pan model with the normal suture size. Strain ratios suggest that shear is an important strain regime in the squamosal suture. This study is consistent with the hypothesis that larger sutures help reduce the likelihood of suture failure under high biting loads. Am J Phys Anthropol 153:260–268, 2014. © 2013 Wiley Periodicals, Inc.